Cryptanalysis of some chaos-based keyed hash functions - ZHENG Shi-hui1; ZHANG Guo-yan3; YANG Yi-xian1; LI Zhong-xian1 (Tongxin xuebao)
By employing the methods including statistic analysis,birthday attacks,and so on,the forging attacks and equivalent-key recovering attacks towards a categories keyed hash functions that are based on chaos systems were pro-posed.Meanwhile,the reasons for that these attacks succeed were analyzed and some suggestions for design keyed hash functions by using chaos systems were summarized.Finally,an improved scheme was presented.The scheme could resist the forging attacks and equivalent-key recovering attacks,while the increased workload could be neglected.